I feel competent and proud when I recall experiential: a self-determination perspective - Rogelio Puente-Díaz¹ (BMC Psychology)
Abstract Consumption is a ubiquitous activity in which consumers satisfy different needs such as the need for competence. In three studies, we tested the influence of type of purchase, material versus experiential, on the satisfaction of the need for competence. In addition, we examined pride and prestige as two consequences. Participants in study 1 were randomly assigned to either recall an experiential or material purchase and completed questions assessing pride and demographics. Results showed a positive influence of experiential purchases on pride. Participants completed a similar battery in study 2 with the addition of the assessment of the need for competence and were randomly assigned to either an experiential or material purchase condition. Results showed a significant indirect effect of experiential purchases on pride by increasing the satisfaction of the need for competence. Last, we manipulated the proposed mediator, need for competence, in study 3 and assigned participants to recall a purchase that made them feel competent or an ordinary purchase and completed the same measures as study 2 with the addition of prestige. Results showed a significant indirect effect of the experimental condition on pride and prestige by increasing first the satisfaction of the need for competence.